Genome‐wide association study of INDELs identified four novel susceptibility loci associated with lung cancer risk. Issue 10 (31st October 2019) - Dai, Juncheng; Huang, Mingtao; Amos, Christopher I.; Hung, Rayjean J.; Tardon, Adonina; Andrew, Angeline; Chen, Chu; Christiani, David C.; Albanes, Demetrius; Rennert, Gadi; Fan, Jingyi; Goodman, Gary; et al.
Abstract : Genome‐wide association studies (GWAS) have identified 45 susceptibility loci associated with lung cancer. Only less than SNPs, small insertions and deletions (INDELs) are the second most abundant genetic polymorphisms in the human genome. INDELs are highly associated with multiple human diseases, including lung cancer. However, limited studies with large‐scale samples have been available to systematically evaluate the effects of INDELs on lung cancer risk. Here, we performed a large‐scale meta‐analysis to evaluate INDELs and their risk for lung cancer in 23, 202 cases and 19, 048 controls. Functional annotations were performed to further explore the potential function of lung cancer risk INDELs. Conditional analysis was used to clarify the relationship between INDELs and SNPs. Four new risk loci were identified in genome‐wide INDEL analysis (1p13.2: rs5777156, Insertion, OR = 0.92, p = 9.10 × 10 −8 ; 4q28.2: rs58404727, Deletion, OR = 1.19, p = 5.25 × 10 −7 ; 12p13.31: rs71450133, Deletion, OR = 1.09, p = 8.83 × 10 −7 ; and 14q22.3: rs34057993, Deletion, OR = 0.90, p = 7.64 × 10 −8 ). The eQTL analysis and functional annotation suggested that INDELs might affect lung cancer susceptibility by regulating the expression of target genes. After conducting conditional analysis on potential causal SNPs, the INDELs in the new loci were still nominally significant. Our findings indicate that INDELs could be potentially functional genetic variants for lung cancer risk. Further functional experiments are needed to better understand INDEL mechanisms in carcinogenesis. Abstract : What's new? Similar to SNPs, short DNA insertions and deletions known as "INDELs" are highly associated with multiple human diseases, including lung cancer. However, they have not been studied systematically. In this large, genome‐wide meta‐analysis, the authors identified four new INDELs that are associated with an increased risk of lung cancer. Functional annotation analysis suggested that INDELs might affect lung cancer susceptibility by regulating the expression of target genes. Further experiments are needed to better understand the molecular mechanisms by which INDELs influence carcinogenesis.